Expanding health justice to consider the environment: how can bioethics avoid reinforcing epistemic injustice? - Pratt, Bridget (Journal of medical ethics, 2023)
We are in the midst of a global crisis of climate change and environmental degradation to which the healthcare sector directly contributes. Yet conceptions of health justice have little to say about the environment. They purport societies should ensure adequate health for their populations but fail to require doing so in ways that avoid environmental harm or injustice. We need to expand our understanding of health justice to consider the environment and do so without reinforcing the epistemic injustice inherent in the field of bioethics. This paper considers what work in philosophy related to the environment should be applied to help build that understanding and develops ideas about the healthcare sector’s responsibilities of justice to the environment. It first introduces the dominant multivalent environmental and ecological justice (EJ) concept in philosophy and each of its dimensions: distribution, participation, recognition and well-being. It then shows why applying that conception alone to broaden our understanding of health justice will reinforce epistemic injustice within bioethics. Drawing on EJ literature from the global South, the paper demonstrates that different ontological and experiential starting points identify additional EJ dimensions—power and harmony—and give rise to a nuanced understanding of the recognition dimension relative to the dominant EJ conception. The paper concludes by applying them to articulate healthcare sector responsibilities of justice to the environment, demonstrating they ground responsibilities beyond reducing its carbon emissions.